Lesson design for formative assessment - Swan, Malcolm; Burkhardt, Hugh (International Society for Design and Development in Education, 2014)
The potential power of formative assessment to enhance student learning is clear from research. This, however, demands a different learning culture and a broader range of teaching approaches than are found in most mathematics classrooms. Earlier efforts to introduce formative assessment for learning have focused on teacher professional development. Here we describe a major project that explores how this change may be stimulated and supported by teaching materials that embody the principles of formative assessment. We describe the design challenges we faced, the previous research and development experience we drew upon, and the principles that directed our designs. We illustrate these elements with examples of the products themselves, some outcomes and lessons learned.